3D Free‐breathing multichannel absolute B1+ Mapping in the human body at 7T. Issue 5 (7th December 2020) - Dietrich, Sebastian; Aigner, Christoph S.; Kolbitsch, Christoph; Mayer, Johannes; Ludwig, Juliane; Schmidt, Simon; Schaeffter, Tobias; Schmitter, Sebastian
Abstract : Purpose: To introduce and investigate a method for free‐breathing three‐dimensional (3D) B 1 + mapping of the human body at ultrahigh field (UHF), which can be used to generate homogenous flip angle (FA) distributions in the human body at UHF. Methods: A 3D relative B 1 + mapping sequence with a radial phase‐encoding (RPE) k‐space trajectory was developed and applied in 11 healthy subjects at 7T. An RPE‐based actual flip angle mapping method was applied with a dedicated B 1 + shim setting to calibrate the relative B 1 + maps yielding absolute B 1 + maps of the individual transmit channels. The method was evaluated in a motion phantom and by multidimensional in vivo measurements. Additionally, 3D gradient echo scans with and without static phase‐only B 1 + shims were used to qualitatively validate B 1 + shim predictions. Results: The phantom validation revealed good agreement for B 1 + maps between dynamic measurement and static reference acquisition. The proposed 3D method was successfully validated in vivo by comparing magnitude and phase distributions with a 2D Cartesian reference. 3D B 1 + maps free from visible motion artifacts were successfully acquired for 11 subjects with body mass indexes ranging from 19 kg/m 2 to 34 kg/m 2 . 3D respiration‐resolved absolute B 1 + maps indicated FA differences between inhalation and exhalation up to 15% for one channel and up to 24% for combined channels for shallow breathing. Conclusion: The proposed method provides respiration‐resolved absolute 3D B 1 + maps of the human body at UHF, which enables the investigation and development of 3D B 1 + shimming and parallel transmission methods to further enhance body imaging at UHF.